Perbandingan Angka Fertilitas dan Hambatan Perkembangan Embrio Mencit yang Dikultur dalam Medium M16 dan Human Tubal Fluid (THE COMPARISON OF MICE FERTILITY RATE AND EMBRYONIC DEVELOPMENT CELL BLOCK WHEN CULTURED IN M16 AND HUMAN TUBAL FLUID MEDIA) - ., Widjiati; Pusporini, Sri Endah; Arifin, M. Zainal (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The aim of this research was to compare the fertility rate and embryonic development cell block ofmice when cultured in M16 and Human Tubal Fluid (HTF) media, respectively. Two months old femaleBalbC mice were super ovulated using Pregnant Mare Serum Gonadotrophin (PMSG) and Human ChorionicGonadotrophin (HCG) prior to mating with vasectomies mice. At 17 hours post mating the mice wassacrificed for the collections of egg cells and spermatozoa. Egg cells were collected by tearing the fertilizationsac, while the sperm were collected from caudal epididymis. After the collection, both the egg cells andsperm were put in Petri dish containing M16 and HTF media and kept in 5% CO2 incubator at 370C for onehour prior to the in vitro fertilization (IVF) was performed. In vitro fertilization was performed in 5% CO2 incubator at 370C and kept for 24 hours in M16 and in HTF culture media. The results showed thatfertilization rate was 98.09% and 99.57%; cell block embryonic development was 85.09% and 83.36%when cultured in M16 and HTF media, respectively. In conclusion, HTF media can be used for culturingmouse embryo.
Keywords: M16 media, HTF media, fertilization rate, cell block